Beyond literal commands in prophetic messages: Reinterpreting imperative meanings in Mukhtār al-Aḥādīth al-Nabawīyah wa-al-Ḥikam al-Muḥammadīyah - Nadina Sanraida Kedaton; Dayudin; Ihin Solihin (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2026)
The hadith corpus is a rich linguistic resource, but remains underexplored for its use of imperatives, whose meanings go far beyond the literal command. Prior scholarship has been predominantly confined to the Qur'anic text or to cross-thematic samples, and no study has systematically examined the meaning of imperatives in a thematic chapter of a classical hadith book, especially from the perspective of ʿilm al-maʿānī. This study addresses the gap by examining the pattern and meaning of imperatives (amr) in Mukhtār al-Aḥādīth al-Nabawīyah wa-al-Ḥikam al-Muḥammadīyah, specifically in the chapter Khātimah fī Tahdhīb al-Nufūs. Data were collected using the observation note technique and analyzed using the distributional method via substitution. A total of 103 imperatives were identified in three patterns: fiʿl al-amr (90), al-fiʿl al-muḍāriʿ bi lām al-amr (11), and ism fiʿl al-amr (2). A notable finding concerns the absence of the maṣdar, one of the four patterns in the ‘ilm al-maʿānī. This absence serves as a stylistic marker that distinguishes this thematic hadith from the Qur'anic imperative patterns. In terms of meaning, reinterpretation reveals the dominance of duʿāʾ (40), followed by ḥaqīqī (30), irshād (28), tahdīd (3), and iltimās (2). The dominance of duʿāʾ and irshād, collectively accounting for 66% of the corpus, demonstrates that imperatives function as a spiritual-pedagogical strategy rather than a binding normative command. These findings contribute to thematic hadith stylistics by establishing an empirical relationship between genre orientation and preference for imperative patterns. From an analytical framework perspective, they also emphasize the importance of the ʿilm al-maʿānī framework for reinterpreting the imperative meaning of hadith.